Responsible corporate governance: An overview of trends, initiatives and state-of-the-art elements. What sort of globalisation is sustainable? - Michael Kuhndt; Burcu Tunçer; Kristian Snorre Andersen; Christa Liedtke (Wuppertal Institut für Klima, Umwelt, Energie, 2003)
Transnational corporations' (TNCs) economic operations cover numerous countriesand can be diverted between several continents. These units have reached a level ofsignificance, having not only economic, but also social and environmental implications. This justifies that they shall be treated separately as a social phenomenon,when considering strategies for the development towards sustainability.This paper presents the concept of Responsible Corporate Governance (RCG), asa strategy to govern TNCs. RCG is suggested as a stakeholder based policyinstrument, which aims at allocating responsibilities to societal actors aiming atcorporate accountability. RCG recognises that the process of societal change isstrongly based on what can be called as bottom up-processes. Learning processestake place through the interaction of the different societal members, whicheventually leads to macro changes. Therefore, governing TNCs towards sustainability improvements is considered to be a collective process including all stakeholders. Firstly, the paper places the concept of RCG in the ongoing debateof political modernization based on the fact that society develops overtime and thepolitical system must correspondingly modernize. In this context, politicaloverload developed as a consequence of increased resource interdependencies isexplained and as a resolution, network approach is discussed. Secondly, demands on the orientation of the TNCs in terms of accountability and innovative actionare brought forward. Here, the paper also lists down corporate elements (stakeholder empowered corporate governance, management and performanceevaluation systems, transparency enhancement and accountability verification), which need to be in place to attain an accountable orientation in the society.Following, using an analytical framework, the orientation and capabilities of each societal actor (environmental non-governmental organisations, financial institutions, intergovernmental organisations) to affect improvements in the corporateresponsibility elements are investigated and recommendations for their effectiveorientation are listed.
urn:nbn:de:101:1-20091020778
Keywords: 330; Corporate Governance; Stakeholder; Nachhaltige Entwicklung; Theorie; Verantwortung